Sex- and reward-dependent effects of early life scarcity-adversity on adolescent behavioral responses to natural rewards - Salazar, Melissa G.; Nguyen, Christine H.; Oak, Sasha; Jackson, Jeffy; Rincón-Cortés, Millie (Frontiers in Behavioral Neuroscience, 2025)
Early life adversity (ELA) increases risk for multiple psychiatric disorders that are characterized by reward-related dysfunction. Disrupted reward-related processes are commonly observed in humans and rodents following ELA. Rodent studies have shown sex differences in response to natural and drug rewards at baseline, following ELA, and in rodent models of psychiatric diseases that are potentiated by ELA. Yet, less is known regarding the development of ELA-induced alterations in reward-related responses, including how these may differ by sex. To this end, we tested behavioral responses to consummatory and social rewards in control and scarcity-adversity male and female rats using sucrose preference, palatable food consumption, and social play tests during peripuberty and adolescence. Our results suggest no impact of early life scarcity-adversity during peripuberty, but sex- and reward-dependent adolescent effects in which females display reduced sucrose preference whereas males display lower levels of social play solicitations (i.e., dorsal contacts). These findings suggest age-, sex-, and reward-specific effects of early life scarcity-adversity in response to consummatory and social rewards, which appear to emerge during adolescence.